Digital Governance and Economic Efficiency: A Mixed-Methods Analysis of Stakeholder Asymmetry in West Lombok's Bureaucratic Reform - Pahrizal Iqrom; Abdurrahaman; Hafizin Hafizin (Lembaga Bale Literasi, 2026)
Digital transformation in government administration has become a strategic agenda for bureaucratic reform. This study analyzes the economic efficiency of digital governance implementation and identifies stakeholder asymmetry in the bureaucratic reform of West Lombok Regency. Using a mixed-methods approach with qualitative case study and quantitative efficiency analysis, data were collected through in-depth interviews, observation, and document analysis at three public service units. Results indicate 71.4% time efficiency, 40% operational cost reduction, and positive return on investment of 47.6% within three years. Stakeholder analysis using the Hexahelix framework reveals asymmetric dependency: government agencies dominate while rural communities and MSMEs remain in high dependency positions, potentially creating digital poverty traps with an estimated annual benefit loss of Rp1.2 billion. The conclusion emphasizes that sustainable digital governance requires balancing technological maturity with social inclusion strategies to prevent technocratic exclusion